Ownership of National Health Insurance and Its Relationship with Delivery by "Dukun Paraji" - Theresia Dessy; Feva Tridiyawati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
In the last decade the government has insisted that every delivery be assisted by health workers in order to reduce maternal mortality and infant mortality. However, there are still many maternity mothers who prefer dukun paraji (shamans to help give birth). One factor is concerns about the cost and ownership of national health insurance. The purpose of this study was to analyze the relationship between ownership of national health insurance and childbirth by dukun paraji. This type of research is case-control. The research location is in the working area of the Waringin Kurung Serang Health Center - Banten in June 2023. The study sample was 50 samples of respondents divided into 25 cases of childbirth in dukun paraji and 25 deliveries in health workers. The data collected is data tracing medical records and village midwives' reports on birth attendants from May 2022 to May 2023. The bivariate analysis used is the Chi-Square test. There was a significant relationship between the ownership of national health insurance and childbirth in dukun paraji, the results of the chi-square analysis resulted in odds ratio values (OR: 8.14; 95% Confident Interval 2.29 – 28.90; p value 0.002).